A Study on the effectiveness & Challenges of online classes for teachers and students - Ravi Sankar Mandapaka; Rama Mohan Prakash Nedunuri (Technium Social Sciences Journal, 2020)
Education can be broadly described as an all-round process encapsulating the information on varied topics that are necessary for the learner to know, understand and practice for the benefit of self and society. The process necessarily involves a teacher who imparts the required knowledge and the seeker of knowledge (student) who is bestowed with the required knowledge by the teacher. Dictionary meaning of Education - ‘a process of teaching, training, and learning, especially in schools or colleges, to improve knowledge and develop skills[i] Online or remote learning or training is necessary, and it is common in case of distance learning programs. Whereas, in these days particularly during the lockdown period (i.e. tentatively from March 2020) almost all educational institutions from schools, colleges, and universities have been focusing their vision on online training to their students. Before the pandemic situation, most of these institutions do not have the online teaching experience (either to a teacher or students), though they have been well equipped with internet and technology usage. It means that the situation is not demanded to go away from face-face or classroom teaching. Generally, a situation or scenario will bring some challenges to the direct parties (a teacher and student), and indirect parties administrators, other stakeholders (parents, technology services providers/suppliers). With this in the background, the researcher has conducted this study to understand the nuances of online classes and find the effectiveness with which the online classes are being conducted for various levels of students. For this study, an online questionnaire was prepared and sent to two categories of respondents – Teachers & Students, who are part of these online classes.[i]https://www.oxfordlearnersdictionaries.com/definition/american_english/education, accessed on 30th July 2020